Reentrant cone angle dependence of the energetic electron slope temperature in high-intensity laser-plasma interactions - Nakatsutsumi, M; Kodama, R; Norreys, P; Awano, S; Nakamura, H; Norimatsu, T; Ooya, A; Tampo, M; Tanaka, K; Tanimoto, T; Tsutsumi, T; Yabuuchi, T (2007)
Energy spectra of fast electrons, generated when high-intensity laser pulses irradiated hollow conical targets, have been measured experimentally. It is shown here that the slope temperature of the fast electrons is strongly dependent on the opening angle of the cone, and has a maximum value at 25°. The data confirms optical guiding of the laser pulse, by comparison of the measured electron temperature with ray-tracing calculations that include absorption in plasmas. The enhanced energy flow and intensity induced by optical guiding of the laser pulse inside the cone as a function of the opening angle as well as the f -number of the focusing optics is discussed. © 2007 American Institute of Physics.